A study of electrocardiographic changes in type 2 diabetes patients - Menezes, Sharol Ashma; Delasalle, Anto; ., Arunachalam (International Journal of Research in Medical Sciences, 2017)
Background: Cardiovascular system has been involved in patients with diabetes in various ways. It is very important to know the electrocardiographic changes that can occur in patients with diabetes. Methods: The electrocardiographic changes were studied in 50 cases with diabetes and compared with 50 healthy age and sex matched controls. Results: Among the 18 females and 32 males included in the study, only 10 patients had diabetes of more than 10 years duration. The various electrocardiographic changes were poor progression of R waves (18%), Q waves (10%), bundle branch blocks (8%), QT prolongation (8%), ectopics (6%), axis changes (6%), heart blocks (6%), rate abnormalities (8%) and chamber enlargement (6%). Conclusions: This study reflects that resting ECG should be an integral part of the examination of all patients with diabetes.